Paradigma Transdisipliner Manajemen - Ismail, Ismail; Azmi, Fakhruddin; Daulay, Nurika Khalila (Universitas Batanghari Jambi, 2024)
Building management studies with a transdisciplinary analysis approach provides two roles, namely: First, contributing to the process of deep culturization by placing ethics to build individuals, families and communities based on religious values and normativity prevailing in society. Second, emphasizing the importance of the function of social ethics as a form of value that becomes a paradigm in directing a person to interact with his social environment and also as the main target of worship because it is the estuary of the perfection of concrete and global piety. Transdisciplinary education is built on the basis of reevaluating the role of intuition, imagination, sensitivity and the body in the transmission of knowledge. Thus, the study of management deals with a complex and changing social, economic, political, cultural world which is a natural law. The interrelationship between various complex components is also a law of nature. This research is a research that uses the method of literature study or literature review. Literature study research is a process or activity of collecting data from various literature such as books and journals to compare the results of one study with another. Transdisciplinary implementation is assumed to be a cooperative effort by scientists in solving problems concerning human life. Each scientific discipline in addressing management issues has a different point of view and study based on the strength of the scientific method of each scientific discipline. In this case, the transdisciplinary management paradigm includes the scientific management paradigm, the human relations management paradigm, the human resource paradigm and the principled leadership paradigm.